PERAN ANALISIS JABATAN TERHADAP KINERJA PEGAWAI SEKDA KABUPATEN PROBOLINGGO - Mastina Maksin; Rahma Wati; Nadila Iskina Maulaya (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
The behavior pattern that society expects of someone in a particular position is what is meant by the term "role." Job analysis frequently plays a significant role in an employee's performance within an institution or organization, particularly within the Regional Secretary of Probolinggo Regency. A job analysis is a process that involves a series of activities like parsing, distinguishing, and arranging things so that they can be regrouped in accordance with particular criteria in order to eventually fill vacant positions in an organization or institution. An institution or organization's job analysis will make it simpler for them to assign them to particular positions, which will later have an impact on employees' performance. The quantity and quality of work performed by employees in accordance with their responsibilities is what determines their level of performance. The level of performance of employees, both individually and collectively, has an impact on the organization's success or failure. Performance is measured using instruments developed in studies that rely on performance measures in general and then translated into fundamental behavioral assessments. Keywords: Role, Job Analysis, Employee Performance